2015
DOI: 10.1159/000369940
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Volume/Raw eGFR Ratio for Predicting Contrast-Induced Acute Kidney Injury in Patients Undergoing Percutaneous Coronary Intervention for Myocardial Infarction

Abstract: Background: Considering that contrast medium is excreted through the whole kidney in a similar manner to drug excretion, the use of raw estimated glomerular filtration rate (eGFR) rather than body surface area (BSA)-normalized eGFR is thought to be more appropriate for evaluating the risk of contrast-induced acute kidney injury (CI-AKI). Methods: This study included 2,189 myocardial infarction patients treated with percutaneous coronary intervention. Logistic regression analysis was performed to identify the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…A large series examining cardiac intervention patients developed similar models with unacceptable discrimination when these two concepts were omitted. 27 Infrarenal endovascular AAA repair occurs frequently enough to provide an adequate cohort for the preceding analyses. Evolving process improvement for infrarenal AAA must guide other aortic procedures, particularly complex AAA repair with branched or fenestrated endografts.…”
Section: Discussionmentioning
confidence: 99%
“…A large series examining cardiac intervention patients developed similar models with unacceptable discrimination when these two concepts were omitted. 27 Infrarenal endovascular AAA repair occurs frequently enough to provide an adequate cohort for the preceding analyses. Evolving process improvement for infrarenal AAA must guide other aortic procedures, particularly complex AAA repair with branched or fenestrated endografts.…”
Section: Discussionmentioning
confidence: 99%
“…The current recommendations are to keep the administered contrast to a minimum, which is nonspecific (13,14). Park et al described the use of iodinated contrast:estimated glomerular filtration rate (eGFR) ratio for predicting contrast-induced acute kidney injury (AKI) in patients undergoing percutaneous coronary intervention for myocardial infarction (15), but to date this metric has not been evaluated within the KTR population.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the difference in eGFR between the two groups, renal function-adjusted CV, or the CV/eGFR ratio, was investigated as both a risk factor and a predictive model. Although several studies have used this ratio as a predictor for CA-AKI after percutaneous coronary interventions, [ 11 13 , 21 ] it has not been used during the EVAR procedure for AAA; however, one study had previously reported the CV/eGFR ratio as a useful predictor for CA-AKI occurrence after EVAR. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study in which coronary intervention was performed showed cutoff results in the range of 2.5 to 3.0. [ 11 13 , 21 ] Further research is needed to obtain a standard cutoff value and to estimate the optimal dose of contrast agent.…”
Section: Discussionmentioning
confidence: 99%